High Capacity Transport: Potential for reduction in transportation costs and traffic emissions - Marttinen, Milja (My University, 2022)
Road transportation forms around 80 % of emissions in transportation, which is more than in any other transportation sector. The politics challenges companies to find more sustainable ways to practice business and that makes it crucial to find new solutions also in transportation. This master thesis study high-capacity transportation (HCT) and their emission and cost levels compared to other road vehicles. Benefits of HCTs are based on it’s capability to decrease tonne-kilometres by carrying more cargo in less journeys. HCT’s fit around 200 km² which is over 30 % more than trailers. This is the base for both, emission, and cost savings, which are made with HCTs. This study is conducted as quantitative research with a survey strategy. The targets of the study are to calculate the actual emission and cost savings that have been made annually with HCTs in Finland, and to compare them to previous theory about subject, and to form a picture about what has changed through using HCTs and where the savings are made. The data is collected as a part of a Finland State of Logistics -survey, which was made in co-operation between University of Turku research group and Finnish traffic administration. The theoretical framework of the study is based around HCT’s features in the form of emission and cost efficiency and how they are conducted around the world, emissions in transportation, where the emissions come from and how they can be affected and then cost structures for different road transport types. The finding of the study are that HCTs make savings in both emissions and costs. HCTs save around 19 % of emissions compared to the trailers, and similar findings have been made in earlier studies also. In the cost structure for HCTs, the biggest change compared to other vehicles was that the labor’s share was smaller. The features of HCTs explain well the findings that were made in this study. HCTs are energy efficient because they can transfer more cargo by one drive and when the driving kilometers are decreased, it also means that less working hours from the labor is needed.
Keywords: Supply chain management, High capacity transport, road transportation, emissions in traffic